JEJARING META-SPACE DALAM DINAMIKA EKSISTENSI PKL DI SIMPUL JALAN DRAMAGA RAYA-BABAKAN RAYA - FERY MULYA PRATAMA (Faktor Exacta, 2017)
The presence of street vendors has now become part of the life of the urban community. Behind the existence of street vendors, there are more problems than just mastery of physical space. PKL relationships with other actors and networking among informal economy. The purpose of this research  is to reveal the meta-space as a representation of habitus and interwoven strategies and tactics of the actors in an effort to perpetuate the existence of street vendors. Field findings show, vendors supported by the presence of other actors in the informal economy networks. They also formed small groups as a tangle of strategy-tactics so that they get a bargaining position to negotiate with preman. Shape in response to changing social conditions is an attempt to defend themselves and maintain PKL existence.